2017
DOI: 10.3847/1538-4357/aa6b04
|View full text |Cite
|
Sign up to set email alerts
|

Radial Surface Density Profiles of Gas and Dust in the Debris Disk around 49 Ceti

Abstract: We present ∼0 4 resolution images of CO(3-2) and associated continuum emission from the gas-bearing debris disk around the nearby A star 49 Ceti, observed with the Atacama Large Millimeter/Submillimeter Array (ALMA). We analyze the ALMA visibilities in tandem with the broadband spectral energy distribution to measure the radial surface density profiles of dust and gas emission from the system. The dust surface density decreases with radius between ∼100 and 310 au, with a marginally significant enhancement of s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
128
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(143 citation statements)
references
References 110 publications
(216 reference statements)
11
128
4
Order By: Relevance
“…So far, 49 Ceti is the only example there is where h has been constrained for the gas. Hughes et al (2017) constrained h to be smaller than 0.04 4 and therefore planets with masses similar or larger than Neptune could explain the observed carbon cavities. Note that planets with masses below a few Jupiter masses are currently undetectable through direct methods (e.g.…”
Section: Interaction With Planetsmentioning
confidence: 92%
“…So far, 49 Ceti is the only example there is where h has been constrained for the gas. Hughes et al (2017) constrained h to be smaller than 0.04 4 and therefore planets with masses similar or larger than Neptune could explain the observed carbon cavities. Note that planets with masses below a few Jupiter masses are currently undetectable through direct methods (e.g.…”
Section: Interaction With Planetsmentioning
confidence: 92%
“…For the other detected targets (49 Cet, HD 32297, HD 110058, HD 138813, HD 156623) we used their measured 12 CO line fluxes (see Tab. 1), and by assuming LTE, we adopted 32 K for 49 Cet (Hughes et al 2017), and 20 K for the other sources as the gas excitation temperature in the CO mass calculation. Taking into account that the 12 CO line could be optically thick in these targets and considering the already mentioned caveats about CO mass estimates (see above) we considered our results as lower limits (Tab.…”
Section: Resultsmentioning
confidence: 99%
“…Such high mass planets are clearly ruled out by the observational limits of SPHERE observations that range from ∼ 3M jup at 20 AU to ∼ 1M jup at 110 AU (Choquet et al 2017). For a planet to satisfy these limits, it would need an eccentricity of at least 0.2 to stir out to 250 AU and higher to stir out to the full extent of the disc as now seen by ALMA (> 300 AU, Hughes et al 2017). It is possible though that lower planetary masses would suffice if two or more planets were present in the system (e.g., Lazzoni et al 2018).…”
Section: Applicationsmentioning
confidence: 99%
“…Following Matrà et al (2018), the above has assumed a simplistic model of a smooth disc with a sharp inner and outer edge. Hughes et al (2017) note an alternative possibility suggested by the observations of a narrow ring located at 110 AU combined with a broad disc, where the emission beyond 110 AU is coming from small (possibly primordial) grains and so the disc only needs to be stirred out to the lo-cation of the ring (see also a discussion in Krivov et al 2013). Assuming this is the case, they then show that a planet responsible for this could easily have a mass lower than the observational limits, whilst also having a low eccentricity orbit.…”
Section: Applicationsmentioning
confidence: 99%